Improving measurement of harms from others' drinking: A key informant study on type and severity of harm. Issue 2 (April 2020) - Stanesby, Oliver; Gmel, Gerhard; Graham, Kathryn; Greenfield, Thomas K; Waleewong, Orratai; Wilsnack, Sharon C
Aims: Survey items for measuring harms experienced from others' drinking (AHTO) have been developed primarily to measure type of harm and not severity. However, some type of harms may produce more negative effects than others. We aimed to compare the perceived severity of a comprehensive list of AHTO items to assess consistency in subjective ratings of severity, facilitate a more nuanced analysis and identify strategies to improve measurement of AHTO in epidemiological surveys. Methods: Thirty-six leaders of national alcohol surveys (conducted between 1997 and 2016) from 23 countries rated the typical severity of negative effects on the victim of each of 48 types of AHTO using a scale from zero (no negative effect) to 10 (very severe negative effect). The survey leaders were also asked to provide open-ended feedback about each harm and the severity-rating task generally. Results: Of 48 harm items, five were classified as extreme severity (mean rating ≥ 8), 17 as high (≥ 6 < 8), 25 as moderate (≥ 4 < 6), and one as low (≤ 4). We used two-way random effects models to estimate absolute agreement intraclass correlation coefficients (AA-ICC) and consistency of agreement intraclass correlation coefficients (CA-ICC). Results showed that there was fair to excellent absolute agreement and consistency of agreement among experts' ratings of the severity of harms from others' drinking (single measures CA-ICC = 0.414, single measures AA-ICC = 0.325; average CA-ICC = 0.940, average AA-ICC = 0.914). Harms to children, and harms causing physical, financial, practical, or severe emotional impacts were rated most severe. Conclusions: When designing new AHTO surveys and conducting analyses of existing data, researchers should pay close attention to harms with high perceived severity to identify effective ways to prevent severe AHTO and reduce the negative health and social impacts of AHTO. By inquiring into experts' views on survey items, this analysis involves a first scoping of the sort of questions that should be taken into consideration. In-depth analyses of specific sub-sets of harms and qualitative interviews with victims of severe AHTO are likely to help along this work in the future.